2018
DOI: 10.1007/s10143-018-0987-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of intraoperative perfusion-weighted MRI and 5-aminolevulinic acid in relation to contrast-enhanced intraoperative MRI and 11C-methionine positron emission tomography in resection of glioblastoma: a prospective study

Abstract: The aim of our study was to compare depicted pre-, intra-, and postoperative tumor volume of met-PET, perfusion-weighed MRI (PWI), and Gd-DTPA MRI. Further, to assess their sensitivity and specificity in correlation with histopathological specimen. Inclusion criteria of the prospective study were histological confirmed glioblastoma (GB), age > 18, and eligible for gross total resection (GTR). Met-PET was performed before and after surgery. Gd-DTPA MRI and PWI were performed before, during, and after surgery. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The authors concluded that these modalities provide different information; however, they did not study the performance of these imaging modalities combined [ 56 ]. In another study of 18 GBMs, Pala et al obtained MET PET and PWI scans asynchronously before, during (MRI only), and after surgery in order to compare tumor volume and diagnostic accuracy compared to histopathology [ 57 ]. Similar to Beppu et al, they found that before gross total resection, MET PET yielded a larger tumor volume than PWI, a difference that disappeared after surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that these modalities provide different information; however, they did not study the performance of these imaging modalities combined [ 56 ]. In another study of 18 GBMs, Pala et al obtained MET PET and PWI scans asynchronously before, during (MRI only), and after surgery in order to compare tumor volume and diagnostic accuracy compared to histopathology [ 57 ]. Similar to Beppu et al, they found that before gross total resection, MET PET yielded a larger tumor volume than PWI, a difference that disappeared after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…MET PET demonstrated higher sensitivity for GBM detection (95%) than PWI (67%). The authors did not explore the question of combining modalities [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, different studies also correlated PET imaging with visible 5-ALA fluorescence in diffusely infiltrating gliomas (36,92,(95)(96)(97)(98). In this sense, Stockhammer et al first reported in 2009 that the standardized uptake value of PET related to normal brain using 18 F-fluoroethyl-L-tyrosine (FET) was significantly higher in tumor areas with 5-ALA fluorescence as compared to normal brain with absence of visible fluorescence (95).…”
Section: -Ala Fluorescence and Pet Imagingmentioning
confidence: 99%
“…Multiple studies compared 5-ALA with amino acid PET and iMRI for the detection of tumor tissue. All but one of the PET studies found a higher sensitivity for PET [ 20 , 65 ] or residual post-operative tracer uptake after complete resection of 5-ALA [ 42 , 59 ]. It has to be mentioned that these were all retrospective studies with different thresholds or qualitative interpretation of tracer uptake.…”
Section: Imaging Techniques For the Guidance Of Glioma Resectionmentioning
confidence: 99%